Pengaruh Penerapan Experiential Marketing terhadap Pelanggan di Rumah Makan Lesehan Joyo Taman Pinang Sidoarjo - Mudji Astuti; Gresivonda Gresivonda (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2014)
Personal experiences help consumers to be linked with brand or product and company as well as inform their purchasing decisions. Conditions of experiential marketing are the actual consumer experience with brands, products or services that can increase sales, brand image and brand awareness through senses, feeling, think, act and relate. Telling consumers about the features and usability of a product or service is quite different with letting them get the experiences by using the product or service themselves. If experiential marketing could be applied in the marketing activity of a firm, then it can be a great tool to increase its brand loyalty. This research is conducted by observing the influence of Experiential Marketing (EXEM) implementation to customer satisfaction at Joyo Restaurant in Taman Pinang Sidoarjo, both partially and simultaneously. Five independent variables – such as sense, feel, think, act, and relate – are used in this research based on Strategic Experiental Modules (SEMs), with customer satisfaction as the dependent variable. The data of 100 customers of the restaurant – as the samples – is analyzed with multiple regresion analysis. Using the t test and F test to test the hypothesis at the 5% significance level, the result shows that sense, feel, think, act and relate significantly affect customer satisfaction. With adjusted R square at 48,6%, this proves that customer satisfaction can be explained by the variables of Strategic Experiental Modules (SEMs), while the remaining 51,4% is explained by other variables.